Seasonal Variation of Birds Species Diversity at Vindhyachal Forest Reserve Khargone, District (M.P.) - Pandey, Praveer; Shrivastava, C.S.; Gaherwal, S. (International Journal of Scientific Research in Biological Sciences, 2020)
The main aim of the present investigation was to study the seasonal variation of birds species diversity at vindhyachal forest reserve at khargone district (M.P.). Seasonal variation of birds species were observed from all the four sites (Wachoo point at Mandleshwar, Jamghat Temple at main Vindhyachal, Double golai Balwada and Gavalan Pati Charbhuja temple Katkut). Several species were observed in different season in the present study. Total forty eight species at Wachoo point, fifty three species at Jamghat Temple, forty four species at Double Golai Balwada and sixty species at Gavalan Pati Charbhuja temple Katkut were recorded during the different season.